Reactive Arthritis Following Intravesical Instillation of Bacillus Calmette-Guerin - Selin HASSAN,; Peyman YALÇIN,; Şebnem ATAMAN,; Nurben SÜLDÜR, (Archives of Rheumatology, 2014)
Reactive arthritis is a seronegative, HLA-B27-linked spondyloarthropathy which occurs as a result of a pathogen, often of gastrointestinal or genitourinary origin, and triggers a cell-mediated immune response. In this article, we present a 64-yearold male case who developed reactive arthritis with fever and asymmetric oligoarthritis following treatment with intravesical Bacillus Calmette-Guerin (BCG) for bladder carcinoma.